Interaction of Citrinin with Human Serum Albumin - Poór, Miklós (Toxins (Basel), 2015)
Citrinin (CIT) is a mycotoxin produced by several Aspergillus, Penicillium, and Monascus species. CIT occurs worldwide in different foods and drinks and causes health problems for humans and animals. Human serum albumin (HSA) is the most abundant plasma protein in human circulation. Albumin forms stable complexes with many drugs and xenobiotics; therefore, HSA commonly plays important role in the pharmacokinetics or toxicokinetics of numerous compounds. However, the interaction of CIT with HSA is poorly characterized yet. In this study, the complex formation of CIT with HSA was investigated using fluorescence spectroscopy and ultrafiltration techniques. For the deeper understanding of the interaction, thermodynamic, and molecular modeling studies were performed as well. Our results suggest that CIT forms stable complex with HSA (logK ~ 5.3) and its primary binding site is located in subdomain IIA (Sudlow’s Site I). In vitro cell experiments also recommend that CIT-HSA interaction may have biological relevance. Finally, the complex formations of CIT with bovine, porcine, and rat serum albumin were investigated, in order to test the potential species differences of CIT-albumin interactions.